The Integration of Eco-Theology in Sekolah Alam Yogyakarta: A Living Quran: Integrasi Eco-Theology di Sekolah Alam Yogyakarta: Sebuah Living Quran - Dwi Ratnasari; Luqyana Azmiya Putri; Febri Widiandari; Adhi Setiyawan (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan Colaboration with Persatuan Pranata Laboratorium Pendidikan Indonesia Tingkat Nasional, 2024)
Purpose – This study aims to explore the integration of eco-theology in the Natural School of Yogyakarta, also known as Nurul Islam Integrated Islamic Elementary School. The research investigates how eco-theology is incorporated into the school’s activities, particularly those related to environmental awareness. Design/methods/approach – The study employs the concept of